HUBUNGAN SIFAT PEMESINAN DENGAN BERAT JENIS DAN JUMLAH PORI EMPAT JENIS KAYU KURANG DIKENAL ASAL KALIMANTAN TIMUR - Achmad Supriadi; Osly Rachman (Jurnal Penelitian Hasil Hutan, 2003)
Machining properties  of four lesser known wood species originated from  natural forest  in East Kalimantan  were studied.  The  relationship  between  machining defects and specific gravity  and amount of  vessel was also  analyzed. The machining operations were planing,  shaping,  boring, turning  and sanding.The result revealed that machining properties were significantly affected by wood species. The machining qualities of lansat hutan (Lansium sp.),  telisai  (Planchonia  grandis   Ridl.) and rambai punai  (Glochidion philippicum  Robins.) woods with respect to criteria were good lo very good, while those nyaling (Mastixia   trichomata  Bl.) fair to very  good.  Either specific gravity or number of vessel was significantly related  with the   machinability 's  defect- free values.  Higher specific gravity tended the higher  the machining qualities. Conversely, greater number of vessels brought about the lowering of machining properties.